Prevalence and determinants of metabolic syndrome among long-shift healthcare professionals in primary hospitals of Central Gondar Zone, Northwest Ethiopia - Elias Chane; Yilkal Amlaku; Amare Mekuanint; Abebaw Worede; Habtamu Wondifraw Baynes; Getnet Fetene (PLoS ONE, 2026)
Background Metabolic syndrome (MetS) is a group of interrelated metabolic aberrations that significantly elevates the risk of poor cardiovascular outcomes and type 2 diabetes mellitus. Healthcare professionals, particularly those working long shifts, may have elevated risk due to the demanding nature of their work, irregular lifestyles, and associated stress. This study aimed to assess the prevalence and associated factors of MetS among healthcare professionals working long shifts in primary hospitals in the Central Gondar Zone, Northwest Ethiopia. Methods An institutional-based cross-sectional study was conducted among a total of 271 healthcare professionals working in three primary hospitals (from September to December 2023). Study data were collected using structured questionairs, anthropometric measurements, and biochemical assessments. Five mililiters of fasting blood sample was collected from each participant; and serum lipid profile and glucose analyzed on Beckman Coulter DXC 700 AU chemistry analyzer. MetS was defined using the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III) criteria. Independent ttest and one-way ANOVA were used for intra and inter group comparison; and Logistic regression model was fitted to identify factors associated with MetS, and adjusted odds ratios (AORs) with 95% confidence intervals (CIs) were reported to determine the strength of associations. Results The prevalence of MetS among healthcare professionals was 11.44% (95% CI 8.14–15.83). Dyslipidemias were observed to be the most common forms of metabolic derangement with 145 (53.51%) of study subjects having at least one lipid profile abnormality; whereas, hyperglycemias was the least common 27 (9.96%) form of metabolic abnormalities. Age ≥ 35 years (AOR = 6.75; 95% CI: 2.34–19.46), a family history of diabetes among first-degree relatives (AOR = 7.78; 95% CI: 2.57–23.53), and short sleep duration (<6 hours per day) (AOR = 7.78; 95% CI: 2.35–25.70) were significant factors associated with MetS (p < 0.05). Conclusion and recommondation Metabolic syndrome is prevalent among healthcare professionals particularily those working long shifts; with age, family history of diabetes, and insufficient sleep identified as key risk factors. Hospital administrators and occupational health units should implement routine metabolic screening, optimized shift scheduling, and sleep hygiene support programs specifically for healthcare professionals working prolonged shifts, with particular attention to high-risk staff groups. Further workplace-based research is also needed to evaluate the effectiveness of these targeted interventions.